Analisis Kualitas Pelayanan Pasien Jamkesmas Rawat Jalan di RSUD Kabupaten Sukoharjo - Atika Sari; Hesti Lestari; Dyah Lituhayu (Journal of Public Policy and Management Review, 2014)
RSUD Kabupaten Sukoharjo is refferal hospital for Jamkesmas patients. The implementasion of Jamkesmas based on the Ministry of Health Regulation No. 40 in 2012. The issue of outpatient Jamkesmas service is about difference Jamkesmas patient and general patient services. This research to describe and analyze the quality of outpatient Jamkesmas service and dimensions that support and obstruct it. This research use the qualitative descriptive methods. This research based on the six dimensions of Zheitmal et al, Salim & Woodward and Lenvinne theory. Tangibles, there was no difference in the use of infrastructure. Reliability, the ability of employe to serve adjusted the skill and training supports. Responsiveness, less respons to accept complaint and suggestion from patients. Courtessy, It has not shown friendly attitude, polite and responsive. Equity, there was still a difference service by the attitude, counter, drugs and procedures. Accountability, there was no evidence transparency of employe service. The Conclusion is quality of outpatient Jamkesmas service still unsatisfactory. The Advice is given to obstacle dimension of service by increasing the use of criticism and suggestion facilities , employe serve heartedly, there is no difference service and give the evidence of service.